PRAGMATIC CHARACTERISTICS OF PHRASAL VERBS IN ENGLISH TEACHING (Universal International Scientific Journal, 2026)
The article examines the pragmatic properties of phrasal verbs in modern Englishwithin the context of teaching English as a foreign language. Special attention is paid to the role ofcontext, extralinguistic and sociocultural factors in interpreting the meanings of phrasal verbs andpreventing pragmatic failure among language learners. The study also addresses the problem ofphrasal verb polysemy and their predominant use in informal spoken discourse, which often causessignificant difficulties in the learning process. The article emphasizes the importance of integratingpragmatic and connotative aspects of phrasal verbs into English language teaching methodology.
Keywords: phrasal verbs; pragmatics; English language teaching